Magnetic Otto Engine for an Electron in a Quantum Dot: Classical and Quantum Approach - Alvarado-Barrios, G (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
We studied the performance of classical and quantum magnetic Otto cycle with a working substance composed of a single quantum dot using the Fock-Darwin model with the inclusion of the Zeeman interaction. Modulating an external/perpendicular magnetic field, in the classical approach, we found an oscillating behavior in the total work extracted that was not present in the quantum formulation.We found that, in the classical approach, the engine yielded a greater performance in terms of total work extracted and efficiency than when compared with the quantum approach. This is because, in the classical case, the working substance can be in thermal equilibrium at each point of the cycle, which maximizes the energy extracted in the adiabatic strokes. © 2019 by the authors.